(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the association between proton pump inhibitor use and atrophic gastritis, and to identify potential risk factors associated with gastric atrophy at the University of Medicine and Pharmacy Hospital, Ho Chi Minh City. Additionally, the study evaluates the correlation between proton pump inhibitor use and atrophic gastritis, along with other risk factors. Subjects and methods: This was a cross-sectional descriptive study involving 300 patients at the University Medical Center Ho Chi Minh City, from January 2022 to January 2024. Data were collected from medical records and direct interviews, and analyzed using SPSS 20.0 software. Results: The average age of the patients was 48.5 ± 13.5 years, with the majority being female. A total of 129 patients (43%) were diagnosed with atrophic gastritis, primarily of mild severity (73.6%). Proton pump inhibitor use was recorded in 98 patients (32.7%), with 12 patients using proton pump inhibitor long-term. Although no clear association was found between long-term proton pump inhibitor use and atrophic gastritis (OR = 1.341; p = 0.618), patients treated with Esomeprazole 20 mg twice daily had a 5.015-fold higher risk of developing atrophic gastritis (95% CI: 1.938-12.982, p = 0.001). Additionally, other factors that statistically increased the risk of atrophic gastritis (p < 0.05) included older age, smoking, alcohol consumption, and H.pylori infection. Conclusion: Long-term use of proton pump inhibitor, particularly Esomeprazole, may significantly increase the risk of developing atrophic gastritis. Other factors such as older age, smoking, alcohol consumption, and H.pylori infection also contribute to the risk. Therefore, closer monitoring is required for patients using long-term proton pump inhibitor, especially when these risk factors are present.